Natural selection shaped the evolution of amino acid usage in mammalian toll like receptor genes. (April 2022) - Ghosh, Manisha; Basak, Surajit; Dutta, Shanta
Abstract : Abstract: Toll-like receptors (TLRs) are important as they are able to sense diverse set of pathogens associated molecular patterns (PAMPs) as ligands. These receptors are involved in functions such as immune response, development of signaling process and cell adhesion. In the present study we are interested to analyze the influence of evolutionary selection pressure on the mutational diversity of mammalian TLR genes. We observed differential patterns of amino acid usage between primate and non-primate mammalian TLR genes. GC-content of TLR genes and hydrophobicity of the encoded proteins are the most influential factors correlated with the differential pattern of amino acid usage.The influence of the subcellular location on the amino acid usage pattern of TLRs is evident in present study. Purifying selection is uniformly present on TLR genes, positively selected sites are mostly located over the ligand binding domain. Our study clearly demonstrates that natural selection has shaped the evolution of primate and non-primate mammalian TLR genes. Abstract : Graphical Abstract: ga1 Abstract : Highlights: A comprehensive evolutionary analysis of toll-like receptors (TLRs) genes. Evolutionary significance of various TLR genes. Evidences for the contributions of TLR genes in response to host defense. Influence of the subcellular location on the amino acid usage pattern of TLRs.